URGENSI PENGELOLAAN KURIKULUM YANG BERMUTU DALAM MENCIPTAKAN PESERTA DIDIK YANG UNGGUL - Arzety Putri Paramita; Meita Rohmatina Fadilah; Tin Rustini (STKIP Subang, 2023)
Education as an effort to educate the nation plays an important role in bringing individual learners to achieve the optimal ability of their potential as indicated by the resulting achievements. Therefore, this research was conducted with the aim of providing an overview of how the implemented curriculum management system plays a role in creating excellent students. The methods used in this research are through a qualitative approach with literature study techniques. The research showed that there is a positive correlation between curriculum management and the creation of excellent students, through the involvement of relevant parties who play a role in the educational process from the beginning of the quality curriculum management process designed until the evaluation process is carried out.